The prognostic impact of obstructive lung disease on survival of never smokers with resected non-small-cell lung cancer: a comparison with smokers. (2nd January 2019) - Akamine, Takaki; Tagawa, Tetsuzo; Shimokawa, Mototsugu; Matsubara, Taichi; Kozuma, Yuka; Haratake, Naoki; Takamori, Shinkichi; Toyokawa, Gouji; Maehara, Yoshihiko
Abstract: OBJECTIVES: The proportion of never smokers among non-small-cell lung cancer (NSCLC) patients has steadily increased in recent decades, suggesting an urgent need to identify the major underlying causes of disease in this cohort. Chronic obstructive pulmonary disease is a risk factor for lung cancer in both smokers and never smokers. The aim of this study was to investigate the association between obstructive lung disease and survival in never smokers and smokers with NSCLC after complete resection. METHODS: We retrospectively reviewed data from 548 NSCLC patients treated at our institution. The effects of obstructive lung disease on recurrence-free survival and cancer-specific survival following the resection of NSCLC were determined by univariable and multivariable Cox regression analyses. RESULTS: Among the 548 patients analysed, 244 patients (44.5%) were never smokers and 304 patients (55.4%) were current or former smokers. In the never-smoker group, 48 patients (19.7%) had obstructive lung disease, 185 patients (75.8%) were women and 226 patients (92.6%) had adenocarcinoma. Obstructive lung disease was significantly associated with shorter recurrence-free survival ( P  =   0.006) and cancer-specific survival ( P  =   0.022) in the never smokers, but not the smokers, on both univariable and multivariable analyses. The associations between obstructive lung disease and prognosis in never smokers remained significant after propensity score matching. CONCLUSIONS: Obstructive lung disease is an independent prognostic factor for recurrence-free survival and cancer-specific survival in never smokers, but not in smokers, with NSCLC. Based on this finding, further examination is warranted to advance our understanding of the mechanisms associated with NSCLC in never smokers.